PENDIDIKAN GURU AGAMA ISLAM DI PERGURUAN TINGGI UMUM NEGERI (Studi Komparatif antara Universitas Negeri Jakarta (UNJ) dengan Universitas Pendidikan Indonesia (UPI) Bandung) - Munadi, Mohammad (IAIN Ponorogo, 2017)
This study examines in depth the design and preparation process of PAI (Education of Islamic Religious) teacher candidates from the curriculum composition. This research uses research method of curriculum text study that exist in two institutions preparing PAI teacher that is Universitas Negeri Jakarta (UNJ) and Universitas Pendidikan Indonesia (UPI) Bandung. The text under study is the curriculum that is on the web of each college. Data analysis using qualitative descriptive technique. The results of research include the following: First, the preparation of Islamic religious education teachers both in UPI Bandung and UNJ focus on strengthening the mastery of Islamic content than the provision of learning methodology materials. But the different depths, UPI more in-depth study of Islam because it is a study program while the UNJ is concentrated. Second, the concept of pedagogical content knowledge as an alternative bid that must be developed by LPTK in graduated professional teachers who have a balance in mastery of material and pedagogic abilityØªØ¯Ø±Ø³ ÙØ°Ù Ø§ÙØ¯Ø±Ø§Ø³Ø© Ø¨Ø¹Ù Ù Ø¹Ù ÙÙØ© ØªØµÙ ÙÙ ÙØ¥Ø¹Ø¯Ø§Ø¯ Ø§ÙÙ Ø±Ø´ØÙÙ ÙÙ Ø¹ÙÙ Ù Ø§ÙØ¯ÙÙ Ø§ÙØ¥Ø³ÙØ§Ù Ù Ù Ù Ù ÙØ¸ÙØ± ØªÙÙÙÙ Ø§ÙÙ ÙØ§ÙØ¬ Ø§ÙØ¯Ø±Ø§Ø³ÙØ©. Â ÙØ³ØªØ®Ø¯Ù ÙØ°Ø§ Ø§ÙØ¨ØØ« Ù ÙÙØ¬ Ø¯Ø±Ø§Ø³Ø© ÙØµ Ø§ÙÙ ÙØ§ÙØ¬ Ø§ÙØ¯Ø±Ø§Ø³ÙØ© Ø§ÙØªÙ ØªÙØ¬Ø¯ ÙÙ Ø§ÙØ¬Ø§Ù Ø¹ØªÙÙ Ø§ÙÙØªØ§Ù ØªÙÙÙ Ø§Ù Ø¨Ø¥Ø¹Ø¯Ø§Ø¯ Ù Ø¹ÙÙ Ù Ø§ÙØ¯ÙÙ Ø§ÙØ¥Ø³ÙØ§Ù Ù ÙÙÙ Ø§ Ø¬Ø§Ù Ø¹Ø© Ø¨ÙØ¯ÙÙØ¬ Ø§ÙØÙÙÙ ÙØ© ÙÙØªØ±Ø¨ÙØ© ÙØ¬Ø§Ù Ø¹Ø© Ø¬Ø§ÙØ±ØªØ§ Ø§ÙØÙÙÙ ÙØ©. Â Ø§ÙÙØµ ÙÙØ¯ Ø§ÙØ¯Ø±Ø§Ø³Ø© ÙÙ Ø§ÙÙ ÙØ§ÙØ¬ Ø§ÙØªÙ ÙÙ Ø¹ÙÙ Ø´Ø¨ÙØ© Ø§ÙØ¥ÙØªØ±ÙØª Ù Ù ÙÙØªØ§ Ø§ÙØ¬Ø§Ù Ø¹ØªÙÙ. ÙØªØÙÙÙ Ø§ÙØ¨ÙØ§ÙØ§Øª Ø¨Ø§Ø³ØªØ®Ø¯Ø§Ù ØªÙÙÙØ© ÙØµÙÙØ© Ø§ÙÙÙØ¹ÙØ©. ÙØªØ´Ù Ù ÙØªØ§Ø¦Ø¬ Ø§ÙØ¨ØØ« Ù Ø§ ÙÙÙ: Ø£ÙÙØ§Ø Ø¥Ù Ø¥Ø¹Ø¯Ø§Ø¯ Ù Ø¹ÙÙ Ù Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ¯ÙÙÙØ© Ø§ÙØ¥Ø³ÙØ§Ù ÙØ© ÙÙ ÙÙ Ù Ù Ø¬Ø§Ù Ø¹Ø© Ø¨ÙØ¯ÙÙØ¬ Ø§ÙØÙÙÙ ÙØ© ÙÙØªØ±Ø¨ÙØ© ÙØ¬Ø§Ù Ø¹Ø© Ø¬Ø§ÙØ±ØªØ§ Ø§ÙØÙÙÙ ÙØ© ØªØ±ÙØ²Ø§Ù Ø¹ÙÙ ØªØ¹Ø²ÙØ² Ø¥ØªÙØ§Ù Ø§ÙÙ ØØªÙÙ Ø§ÙØ¥Ø³ÙØ§Ù Ù Ø¨Ø§ÙÙØ³Ø¨Ø© Ø¥ÙÙ ØªÙÙÙØ± Ù ÙØ§Ø¯ Ù ÙÙØ¬ÙØ© Ø§ÙØªØ¯Ø±ÙØ³. ÙÙÙÙ Ø§ÙØ£Ø¹Ù Ø§Ù Ø§ÙÙ Ø®ØªÙÙØ©Ø ÙØ§ÙØª Ø¬Ø§Ù Ø¹Ø© Ø¨ÙØ¯ÙÙØ¬ Ø£ÙØ«Ø±Ø§ÙØªÙ Ø§Ù Ø§ Ø¨Ø¯Ø±Ø§Ø³Ø© Ù ØªØ¹Ù ÙØ© ÙÙØ¥Ø³ÙØ§Ù ÙØ£ÙÙ ÙÙ ÙØ³Ù Ø§ÙØ¯Ø±Ø§Ø³Ø© ÙÙ ØÙÙ Ø¬Ø§Ù Ø¹Ø© Ø¬Ø§ÙØ±ØªØ§ Ù Ø¬Ø±Ø¯ Ø´Ø¹Ø¨Ø© Ù Ù Ø§ÙÙØ³Ù . Ø«Ø§ÙÙØ§Ø Ù ÙÙÙÙ Ù Ø¹Ø±ÙØ© Ø§ÙÙ ØØªÙÙ Ø§ÙØªØ±Ø¨ÙÙ ÙÙ ØØ§ÙÙØ© Ø¨Ø¯ÙÙØ© Ø§ÙØªÙ ÙØ¬Ø¨ ØªØ·ÙÙØ±ÙØ§ Ù Ù ÙØ¨Ù ÙØ¨ØªÙ (LPTK) ÙÙ ØªØ®Ø±ÙØ¬ Ø§ÙÙ Ø¹ÙÙ ÙÙ Ø§ÙÙ ÙÙÙÙÙ Ø§ÙØ°ÙÙ ÙØ¯ÙÙÙ ÙÙØ§Ø¡Ø© Â ÙÙ Ø¥ØªÙØ§Ù Ø§ÙÙ ÙØ§Ø¯ ÙØ§ÙÙ ÙØ§ÙØ¬ Ø§ÙØªØ±Ø¨ÙÙØ©.